Transgenerational Epigenetic Inheritance of Longevity in C. elegans - Greer, Eric L. (2011)
Chromatin modifiers regulate lifespan in several organisms, raising the question of whether changes in chromatin states in the parental generation could be incompletely reprogrammed in the next generation and thereby affect the lifespan of descendents. The histone H3 lysine 4 trimethylation (H3K4me3) complex composed of ASH-2, WDR-5, and the histone methyltransferase SET-2 regulates C. elegans lifespan. Here we show that deficiencies in the H3K4me3 chromatin modifiers ASH-2, WDR-5, or SET-2 in the parental generation extend the lifespan of descendents up until the third generation. The transgenerational inheritance of lifespan extension by members of the ASH-2 complex is dependent on the H3K4me3 demethylase RBR-2, and requires the presence of a functioning germline in the descendents. Transgenerational inheritance of lifespan is specific for the H3K4me3 methylation complex and is associated with epigenetic changes in gene expression. Thus, manipulation of specific chromatin modifiers only in parents can induce an epigenetic memory of longevity in descendents.